The impact of sports tourism in the urban development of some Spanish cities. A review of their sports and tourism policies - Nebot-Gómez-de-Salazar, Nuria; López-Bravo, Celia; Rosa-Jiménez, Carlos (Cambridge Scholars Publishing, 2022)
The purpose of this research is to analyse how sports and tourism strategic planning have contributed to the urban and territorial development of some Spanish cities and tourist destinations in the Mediterranean area. This paper delves into the relationship between sports, city design and tourism. To this end, a review has been developed of some of the Spanish urban, tourist and sports policies that incorporate this relationship and may be a reference for other administrations and policies. The work is divided into two approaches: the analysis of integrated sports policies in different Spanish urban areas which include urban conditions, as well as tourist policies with urban and territorial implications. The results obtained from this analysis provide, therefore, information about which are the public spaces that favour informal sports practice, how they influence the visitors and the local population and what is their impact on local economies. From these integrated urban, sports and tourist policies as examples of good practices, a classification of public outdoor spaces that favour informal sports practice is established for urban and natural environments.
The Accepted Version may be posted in or linked to by the author’s Institutional Repository at any time after the chapter is accepted.
Keywords: Turismo deportivo; Urbanismo; Desarrollo urbano; informal sports activities; public space; sports policies; tourist policies; urban development